Comparative analysis of two catastrophic hazardous chemical accidents in China. Issue 1 (30th January 2020) - Wang, Jianhao; Fu, Gui; Yan, Mingwei
Abstract: On March 21, 2019, a serious explosion of hazardous chemicals occurred in Tianjiayi Company located in Xiangshui Chemical Industry Park in Yancheng City, Jiangsu Province, China. Seventy‐eight people were killed and 716 were injured. It is the most severe accident since the globally recognized fire and explosion at a hazardous chemical warehouse in Tianjin Port, Tianjin, China in 2015. According to the preliminary analysis of the Yancheng accident and the review of previous studies about the Tianjin Port accident, there are similarities regarding the process of the two accidents. Therefore, in addition to reporting the investigation results of the Yancheng accident, an important aim of this work is to focus on the brief comparative analysis between it and the Tianjin Port accident. The comparisons were mainly conducted according to the basic information of the events, triggers and processes, individual factors, organizational management factors, external regulatory factors, and then the differences and similarities between the two accidents are summarized. Thus, useful lessons in the aspects of the storage and management of hazardous chemicals, safety training and accident learning, implementation of safety management system, government supervision, and so on, can be drawn to avoid similar mistakes within the industry.